MODERN EDUCATIONAL TECHNOLOGIES IN THE THEORY AND PRACTICE OF THE PREPARATION OF HIGHER EDUCATION STUDENTS FOR TEACHING - Artiushyna, Maryna; Sarkisova, Oksana (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article is devoted to the problem of using modern educational technologies in higher education. The purpose of the study was to identify a clear and modern definition of the "educational technology" concept, as well as to substantiate such a classification of modern educational technologies that can be used in the preparation of students of higher education for teaching. The research was based on the use of several theoretical and empirical methods: analysis, comparison and generalization, as well as the study of pedagogical experience and activity products. On the basis of theoretical analysis and comparison, the modern interpretation of the essence of the "educational technology" concept was revealed. Its discrepancy with the concepts of "pedagogical", "educational", "innovative" and "information technology" is shown. The comparison of the most famous classifications of educational technologies described by modern Ukrainian researchers was made. The shortcomings of the existing classifications are identified. The importance of the substantiating a clear classification of modern educational technologies for using it in preparing students for teaching has been proven. Based on the study of the curricula of disciplines used in higher education institutions to prepare future students of higher education for teaching, the practical experience of classifying modern educational technologies was studied. Based on the generalization, the author's classification of modern educational technologies according to the criterion of innovativeness was developed and the experience of its use in the preparation of students of higher education for teaching at the Vadym Hetman Kyiv National University of Economics was described. The results of the study proved the effectiveness of using the offered classification of modern educational technologies in the preparation of students of higher education for teaching. Based on the results of the study, conclusions about the effectiveness and perspective of using the offered classification of modern educational technologies in scientific research and teaching practice were formulated.